Proyecto de Factivilidad para la creaciòn de una Caja de Ahorro en la Parroquia Sabanilla, Cantòn Celica, Provincia de Loja. - Jimbo Ordòñez, Joanna Cecibel (2016)
The "PROJECT FEASIBILITY FOR THE CREATION OF A BOX OF SAVINGS IN SABANILLA, Celica Canton, Loja province PARISH" it has developed in order to improve the family economy, providing affordable financial services for the residents of the parish Sabanilla. To comply with the objectives in the project began with a literature review and the development of different scientific, inductive, deductive, statistical methods. To make the development of the market study the implementation of a survey of the population of the Sabanilla parish to gauge their interest in becoming a partner of the box and the ability to save was made, plus the potential demand and actual demand is calculated 1061 inhabitants to year zero, effective demand for zero year 1053, the supply of 621 for the year zero and 440 partners unmet demand for year 1 are the people who agree with the creation of the savings bank "Altar cloth". The services we provide are housing savings and loans where the lending and deposit rate will be fixed according to the reference by the Central Bank of Ecuador always considering the social order. The technical study determined the size, the location of the savings bank will be on the Sabanilla parish in the Av. Loja streets between November 3 5 and sucre where a local for normal operation providing an efficient and effective service will be leased. In the administrative-legal study the organization of the savings bank, for which manuals, statutes and regulations that indicate the roles and responsibilities to be met by staff from the organization for efficient development of activities outlined settled. For the financial economic study an initial investment of $ 21.505,90 needed to launch the project, the usefulness of the project for the first year is $ 4.905,46 was considered; financing the savings bank will be made by the initial contribution, sight savings and fixed-term savings by the partners. The financial evaluation confirms the viability of the thesis project through its indicators: the NPV is $ 23708,32 means the value of the cash increase, the IRR is 35,73% which shows that the project will have high performance The benefit-cost ratio of 1.51 which indicates that for every dollar invested will get 0.51 of profitability, capital recovery period is 2 years, 11 months and 24 days and the sensitivity analysis with increased costs of 20,38% and revenue decreased 13,51%. Finally the respective conclusions and recommendations necessary to carry out the development of this thesis project was raised.